Corollary Effects: Curation of Quality, Voice and Provocation - Sameshima, Pauline (Journal of the Canadian Association for Curriculum Studies, 2016)
As more curriculum scholars think of curriculum as currere—the dynamic development of self-understanding in the context of conversation and learning with others—and, as storying as a form of research dissemination grows in the curriculum field, I offer some thoughts on the following questions: How do my editorial choices cumulatively affect my community, the field, or me? How does my relationship to quality change? How might questions of quality both inspire and conspire against curriculum as currere? What does quality have to do with academic voice? What are my responsibilities in promoting provocative scholarship? And how might curation create new connections for the readership?